2018
DOI: 10.1039/c7ew00470b
|View full text |Cite
|
Sign up to set email alerts
|

FAMEs production from Scenedesmus obliquus in autotrophic, heterotrophic and mixotrophic cultures under different nitrogen conditions

Abstract: This study investigated the growth and biodiesel production of S. obliquus from autotrophic, heterotrophic and mixotrophic cultures under different nitrogen conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…These results are in line with what was previously reported for S. obliquus ; however, some studies have reported high abundances of EPA in this microorganism, which we do not report [ 69 , 70 , 71 , 72 ]. Nonetheless, variations in cultivation might justify the absence of EPA, as salinity, nitrogen, and nutrient stress affect the composition and yield of FA [ 73 , 74 , 75 , 76 ]. Additionally, the way S. obliquus biomass is processed has been shown to affect the abundance of FA [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with what was previously reported for S. obliquus ; however, some studies have reported high abundances of EPA in this microorganism, which we do not report [ 69 , 70 , 71 , 72 ]. Nonetheless, variations in cultivation might justify the absence of EPA, as salinity, nitrogen, and nutrient stress affect the composition and yield of FA [ 73 , 74 , 75 , 76 ]. Additionally, the way S. obliquus biomass is processed has been shown to affect the abundance of FA [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are essential because your body cannot produce them on its own so they must come from the diet. FAs composition and yield of T. obliquus varies depending on salinity (Salama et al 2013), nitrogen source (An et al 2020), nutrient stress (Chu et al 2014), cultivation mode (Shen et al 2018) or the way in which biomass is processed (explained in Microalgae harvesting and biomass processing section). The main FAs reported for T. obliquus biomass are listed in Table 3.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…In terms of these results, we hypothesize that the LC-PUFAs (ARA or EPA) formulation for five agitation speeds were all deduced via Route 2. In this, LA (C18:2▵9,12) first converts to GLA ( -linolenic acid, C18:3▵6,9,12) by ▵6-desaturation and afterwards to ARA (C20:4▵5, 8,11,14) by C2 elongation and ▵5-desaturation, finally generating EPA (C20:5▵5,8,11,14,17) by 3-desaturation. Moreover the presumption was that the middle agitation speeds (150-300 rpm) reduced the activity of 3-desaturation and thus inhibited the conversion from ARA to EPA, inevitably leading to an increase content of ARA and LA and a decrease in the content of EPA.…”
Section: Formation Of the Lc-pufasmentioning
confidence: 99%
“…On the basis of the results of the basic rheological characterization of P. cruentum suspensions, the relationship between ; GLA: -linolenic acid (C18:3▵6, 9,12); ALA, -linolenic acid (C18:3▵9,12,15); SDA, stearidonic acid (C18:4▵6, 9,12,15); DGLA, di-homo -linolenic acid (C20:3▵8, 11,14); ARA, arachidonic acid (C20:4▵5, 8,11,14); ETA, eicosatetraenoic acid (C20:4▵8, 11,14,17); EPA, eicosapentaenoic acid (C20:5▵5, 8,11,14,17). ▵6 Des, ▵6-desaturation; C2 Elo, C2-elongation; ▵5 Des, ▵5-desaturation.…”
Section: Correlation Between P Cruentum Biomass and Limiting Viscositymentioning
confidence: 99%
See 1 more Smart Citation